2020
DOI: 10.1007/s10067-020-05399-4
|View full text |Cite
|
Sign up to set email alerts
|

Anti-phospholipid syndrome leading to digital ischaemia and rare organ complications in systemic sclerosis and related disorders

Abstract: APS should be considered in all patients with digital ischaemic symptoms • APS may be an important driver of SSc-related digital ulceration/necrosis• Identification of SSc-associated APS opens up new therapeutic options for acute management and secondary prevention

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…APS can present as primary or secondary to other autoimmune disorders, most commonly SLE: approximately 40% of patients with SLE eventually develop APS. 1 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…APS can present as primary or secondary to other autoimmune disorders, most commonly SLE: approximately 40% of patients with SLE eventually develop APS. 1 …”
Section: Discussionmentioning
confidence: 99%
“…APS can be primary or secondary to a previously established disease, of which systemic lupus erythematosus (SLE) is the most common, coexisting in approximately 30% to 40% of cases. 1 APS has a heterogeneous clinical presentation and can involve multiple organs, especially the skin. About 40% of patients present with cutaneous manifestations as the first indication of disease.…”
Section: Introductionmentioning
confidence: 99%
“…APS-related comorbidities in the study population that were considered included diabetes mellitus [ 10 ] (ICD-9-CM 250), hypertension [ 11 13 ] (ICD-9-CM 401–405), hyperlipidemia [ 14 ] (ICD-9-CM 272), stroke [ 10 ](ICD-9-CM 430–438), heart failure [ 15 ] (ICD-9-CM 428), atrial fibrillation [ 16 ] (ICD-9-CM 427.32), myocardial infarction [ 17 ] (ICD-9-CM 410–410.9, 412), peripheral arterial occlusive disease [ 10 ] (PAOD; ICD-9-CM 440–444), chronic kidney disease [ 13 ] (ICD-9-CM 580–589), chronic obstructive pulmonary disease [ 18 ](COPD; ICD-9-CM 490–496), deep vein thrombosis [ 10 ] (ICD-9-CM 451.1, 451.2, 451.8, and 453), pulmonary embolism [ 10 ] (ICD-9-CM 415.1), systemic lupus erythematosus [ 10 ] (SLE; ICD-9-CM 710.0), rheumatoid arthritis [ 19 ] (ICD-9-CM 714), systemic sclerosis [ 20 ] (ICD-9-CM 710.1), Sjogren’s syndrome [ 21 ] (ICD-9-CM 710.2), and polymyositis [ 22 ] (ICD-9-CM 710.4).…”
Section: Methodsmentioning
confidence: 99%
“…ACL and anti-β2-GPI antibodies can contribute to accelerated atherosclerosis by interacting with ECs and inducing a proinflammatory endothelial phenotype (41). Some studies reported an association between aPL positivity and PAH and DU (109)(110)(111)(112)(113), while others did not (108,114,115). Lastly, considering the strong clinical associations of SSc specific antibodies (anticentromere, anti-topoisomerase 1, anti-RNA polymerase III and anti-Th/To antibodies) and their role as prognostic biomarkers, a potential pathogenicity of these antibodies was suggested.…”
Section: Autoantibodiesmentioning
confidence: 99%